Integration of in silico modeling, prediction by binding energy and experimental approach to study the amorphous chitin nanocarriers for cancer drug delivery. (20th May 2016) - Geetha, P.; Sivaram, Amal J.; Jayakumar, R.; Gopi Mohan, C.
Highlights: Curcumin, docetaxel, 5-FU loaded amorphous chitin nanoparticles was prepared. Curcumin drug showed as best carrier for amorphous chitin nanoparticles (AC-NPs). Cytotoxicity and cellular uptake was studied on Gastric cancer cells. In silico binding energy (BE) between AC-NPs and anti-cancer drugs were studied. Computational BEs correlates with experimental loading and entrapment efficiencies. Abstract: In silico modeling of the polymer–drug nanocarriers have now days became a powerful virtual screening tool for the optimization of new drug delivery systems. The interactions between amorphous chitin nanoparticles (AC-NPs) with three different types of anti-cancer drugs such as curcumin, docetaxel and 5-flurouracil were studied by integration of computational and experimental techniques. The drug entrapment and drug loading efficiency of these three drugs with AC-NPs were (98 ± 1%), (77 ± 2%), and (47 ± 12%), respectively. Further, cytotoxicity and cellular uptake studies of drug loaded AC-NPs on Gastric adenocarcinoma (AGS) cells showed enhanced drug uptake and cancer cell death. In silico binding energy (BE) between AC-NPs with these anti-cancer drugs were studied by molecular docking technique. Computational drug's BEs are in excellent agreement with experimental AC-NPs drug loading ( R 2 = 0.9323) and drug entrapment ( R 2 = 0.9741) efficiencies. Thus, present integrated study revealed significant insight on chemical nature, strength, and putative interacting sites of anti-cancer drugs with AC-NPs.